Penerapan Model Pembelajaran Numbered Head Together Pada Mata Pelajaran IPS Siswa Kelas IV SD - Melisa Mahlevi; Rudi Erwandi (Journal of Elementary School (JOES), 2022)
This research was conducted because it saw the social studies learning outcomes of fourth graders at SD Negeri Sukadana which were still low. This study aims to determine the completeness of students' social studies learning outcomes through numbered heads together (NHT) cooperative learning. From the data analysis of student learning outcomes before and after the NHT cooperative learning model was applied, the scores before the NHT cooperative learning model was applied were 100% incomplete. After applying the NHT cooperative learning model, the completeness of the social studies subject learning outcomes were 19 students who completed or 95% and 1 student who did not complete 5%. The data were analyzed using the z-test formula. based on the results of the data analysis test with a confidence level of = 5%, it shows Z_count = 6.42 and Z_(table) = 1.64. Because Z_count > Z_(table ). With that it can be concluded that the learning outcomes of class IV social studies subjects at SD Negeri Sukadana after the application of the numbered head together (NHT) learning model to the learning outcomes of class IV social studies subjects at SD Negeri Sukadana were significantly completed. Keywords: Numbered head together (NHT) learning model, social studies learning outcomes.